Risk factors for diabetic foot ulcers mortality and novel negative pressure combined with platelet-rich plasma therapy in the treatment of diabetic foot ulcers - Wang, Yanling; Liu, Bang; Pi, Yinzhen; Hu, Li; Yuan, Yeling; Luo, Jiao; Tao, Yixiao; Li, Ping; Lu, Shan; Song, Wei (Frontiers in Pharmacology, 2022)
The purpose of this study was to assess the risk factors for morbidity and mortality of diabetic foot ulcers (DFU). For the treatment of DFU, negative pressure wound therapy (NPWT) combined with platelet-rich plasma-fibrin glue (PRP) was also investigated. There were 653 patients in the DFU group and 510 patients in the diabetic patients without foot ulceration (NFU) group, for a total of 1163 patients in the study samples after individuals without follow-up were excluded. The patients were randomized into two groups: the NPWT group and the NPWT combined with the PRP group. The findings of the univariate analysis revealed the blood indicators for predicting DFU morbidity risk factors, such as C-reactive protein, albumin, creatinine, alkaline phosphatase, procalcitonin, platelets, 25-hydroxyvitamin D, β-2-microglobulin, monocyte ratio, low-density protein cholesterol (LDL), triglyceride, alanine aminotransferase (ALT), aminotransferase (AST), Creatine Kinase (CK) and total cholesterol. Using logistic regression analysis revealed only albumin and age to be independent predictors of DFU mortality. Our study also revealed that, compared to NPWT alone, NPWT combined with PRP accelerated wound healing and reduced the mortality rate. According to the findings of this pilot study, new risk factors for DFU morbidity and mortality have been found, and NPWT combined with PRP therapy may provide the first information that it is an effective adjunct treatment for DFU.